Strategi Manajemen Perubahan dalam Meningkatkan Kinerja Pegawai Manakala Coffee (Medan) - Anggita Rizkia; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Change management is a systematic process of implementing knowledge, tools and resources needed to effect change on the people who will be affected by the process. Change management too understood as the efforts taken by managers to manage change effectively, where an understanding of the issues of motivation, leadership, group, conflict, communication and discipline Thus change management should have a good strategy, in accordance with the current situation and conditions will occur. Change management is very appropriate to do in increasing discipline mainly in college. Causes and consequences of change in the organization always results in two things, namely change for the good and change towards destruction. These two things can happen due to several reasons that come from inside and outside the institution concerned. Because change management is a process, tool, and technique for managing people through process of change to improve discipline, so that the goals of the institution can be achieved.